Menyingkap Kearifan Spiritual: Analisis Ritual Nyadran di Makam Raja Mataram Kotagede dengan Pendekatan Teologis - M. Dimyati Huda; Purwadi (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2024)
The Nyadran ritual at the tomb of King Mataram Kotagede is the focus of this research, with the aim of explaining and analyzing the activity through the lens of theological theory. Every Ruwah month, Nyadran ceremony is held by Surakarta Hadiningrat Palace, where the theological aspects are analyzed with descriptive method to reveal the values systematically, integrally, and comprehensively. The main purpose of this ritual is to honor the spirits of the ancestors who played a role in establishing the Mataram Kingdom. The method used is field research. Data collection by means of observation, interviews and documentation. The result of this research is that the Nyadran ritual activities at the tomb of King Mataram Kotagede strengthen the efforts to extract local wisdom values. Exemplary is realized by respecting the struggle of the founders of the Mataram kingdom. Nyadran ceremony at the Tomb of King Mataram Kotagede is not only a customary tradition, but also a commemoration that contains historical, cultural, and spiritual values. The younger generation can emulate the main behavior. Javanese beliefs believe that the spirits of ancestors can provide blessings. Children and grandchildren are also expected to have a purposeful life.